Developing a test of reasoning for preadolescents. Issue 5 (20th October 2022) - Ahmed, Ayesha; Howe, Christine; Major, Louis; Hennessy, Sara; Mercer, Neil; Warwick, Paul
ABSTRACT: As part of an investigation into the relationship between classroom dialogue and student outcome, a test of reasoning has been developed that is suitable for preadolescents (i.e. c.10–13-year-olds). Building on previous work but expanding this considerably, the test focuses upon four areas of reasoning: differentiation of facts from opinions, differentiation of reasons from conclusions, inference of implications, and evaluation of multiple reasons. This paper reports on the test's design and development (including the repeated cycles of piloting and redrafting), highlighting the methodological challenges that were faced (e.g. from linguistic demands), and how these were addressed. It also outlines how the test was trialled in English schools, including its use in a paper-based version with 218 students, and in a digital version with 129 students. Patterns of student performance were comparable across the two samples and also provide evidence for acceptable test reliability and validity. Thus, in addition to spotlighting methodological issues of general relevance within educational research, the paper presents a test that successfully assesses key aspects of student reasoning. The test is the first of its kind to be designed for this age group, and is offered as freely available for future research.